2017
DOI: 10.1093/mnras/stx2079
|View full text |Cite|
|
Sign up to set email alerts
|

A cut-off in the TeV gamma-ray spectrum of the SNR Cassiopeia A

Abstract: It is widely believed that the bulk of the Galactic cosmic rays is accelerated in supernova remnants (SNRs). However, no observational evidence of the presence of particles of PeV energies in SNRs has yet been found. The young historical SNR Cassiopeia A (Cas A) appears as one of the best candidates to study acceleration processes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 49 publications
2
48
0
Order By: Relevance
“…Frequently discussed is, for example, the case β = 1 (see e.g. Ahnen et al (2017)). The hadronic model given by Eq.…”
Section: Models and Hypotheses Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequently discussed is, for example, the case β = 1 (see e.g. Ahnen et al (2017)). The hadronic model given by Eq.…”
Section: Models and Hypotheses Testsmentioning
confidence: 99%
“…The Pevatron nature of a γ-ray source is in turn constrained when an exponential cutoff at an energy well below 100 TeV is detected in the observed γ-ray spectrum of the source. For example, the recent detection of an exponential cutoff at E cut, γ = 3.5 TeV in the γ-ray spectrum of Cassiopeia A rules out simple Pevatron models for this young galactic SNR (Ahnen et al 2017). The most constraining lower limits on the energy cutoff E cut, h of galactic hadron accelerators are currently derived from the diffuse γ-ray emission in the vicinity of the radio source SgrA* and for the γ-ray source HESS J1641-463.…”
Section: Introductionmentioning
confidence: 99%
“…This figure is adapted from figure 2 in Ellison et al (2012) and that paper should be seen for details and references to the observations. Figure 1 from Ahnen et al (2017) ("A cut-off in the TeV gamma-ray spectrum of the SNR Cassiopeia A") showing the spectral energy distribution from the Cassiopeia A SNR. As indicated, the black dots are from the MAGIC telescopes while the blue squares were measured by the Fermi spacecraft.…”
Section: Cosmic Ray Escape In Fermi Accelerationmentioning
confidence: 99%
“…Using 10-year data from INTEGRAL observations, Wang & Li (2016) first extended the nonthermal X-ray spectrum to ∼220 keV without evidence for a high-energy cutoff. In GeV band, it was detected by Fermi-LAT as a point source with a photon index of 1.9-2.4 (Abdo et al 2010;Yuan et al 2013;Saha et al 2014) and a spectral break around 1.7 GeV was reported (Yuan et al 2013;Ahnen et al 2017). As a TeV γ-ray source, it was first detected by HEGRA at 5σ level (Aharonian et al 2001) and was further observed by MAGIC (Albert et al 2007) and VERITAS (Acciari et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Two zone emission models have been proposed for the radio to X-ray morphology and spectra (Atoyan et al 2000b,a) and the nature of the γ-ray emission is still ambiguous (e.g., Yuan et al 2013;Saha et al 2014;Zirakashvili et al 2014). With 158h of high quality data, a high-energy cutoff of ∼ 3.5 TeV in the γ-ray spectrum of Cas A was recently detected by MAGIC with 4.6σ significance (Ahnen et al 2017). This spectral feature seems to disfavor Cas A as a PeV particle accelerator if the TeV γ-ray emission is dominated by hadronic processes.…”
Section: Introductionmentioning
confidence: 99%